Improving service quality offered by lodging industry SMEs located in emerging Peruvian destinations using the Application of Good Practices System - Herrera Marín, Susan (2019)
This paper is the result of the need for SMEs in the lodging industry to improve service quality while remaining cost-effective. The Sistema de Aplicación de Buenas Prácticas [Application of Good Practices System] (SABP) is a tool for SMEs, as it improves quality of services offered and their positioning, leveraging the zone and destination location, in order to optimize the quality of life in the community. Thus, this study proposes an application methodology that adjusts to the progress of said businesses, so that a balance between adequate administrative management processes, service, infrastructure and equipment, collaborator performance, and support areas is found.